2007
DOI: 10.1002/jcu.20346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of altitude on spleen volume: Sonographic assessment

Abstract: Our data show that splenic volume in healthy individuals who begins to live at high altitudes decreases gradually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 19 publications
(22 reference statements)
0
21
2
Order By: Relevance
“…Both our present study and the results cited above seem to be conflicting with a study by Sonmez et al (2007), in which it was reported that long-term exposure to high altitude in lowlanders resulted in reduced splenic volume and increased Hb across 6 months. In that time, substantial altitude acclimatization has elevated Hb via increased erythropoiesis, and it is not clear how this relates to the relatively short-term adjustments seen in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Both our present study and the results cited above seem to be conflicting with a study by Sonmez et al (2007), in which it was reported that long-term exposure to high altitude in lowlanders resulted in reduced splenic volume and increased Hb across 6 months. In that time, substantial altitude acclimatization has elevated Hb via increased erythropoiesis, and it is not clear how this relates to the relatively short-term adjustments seen in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…This formula is often used for predicting the volume of many irregularly shaped organs (Asghar et al, 2011b;Yetter et al, 2003;Sonmez et al, 2007). In literature findings, it was seen that elipsoid formula was used.…”
Section: Discussionmentioning
confidence: 99%
“…Using ultrasonography, Sonmez et al (2007) conWrmed that 3-6 months exposure to altitude through relocation of lowlanders resulted in reduced splenic volume and concomitant increases in Hb and Hct, but no speciWc focus was directed toward the ascent and descent phases. Richardson and associates (2007) discovered that the transient elevation in Hb during apnea was attenuated and eventually disappeared as individuals travelled to progressively higher altitudes, during which time an overall polycythemia occurred.…”
Section: Introductionmentioning
confidence: 97%